Vector J-integral analysis of crack initiation at the edge of complete sliding contact - Ma, L; Korsunsky, A (Royal Society Publishing, 2006)
In this paper, the crack initiation at contact surface of solids is investigated on the basis of the concept of potential energy release rate. The expressions for path-independent integral vector Ji (i=1,2) are derived and applied to the consideration of the process of crack initiation. The relationship is then established between the value of the path-independent integral vector Ji and the potential energy release rate for crack initiation in an arbitrary orientation. This allows the prediction of crack initiation angle on the basis of the maximum energy release rate criterion. The surface crack initiation angle in fretting fatigue is determined analytically as a function of the friction coefficient of the edge contact. This theoretical result is compared with the existing experimental results reported in the literature and a good agreement is found. The formulation provides a novel basis for numerical modelling of the complex process of fretting fatigue.